Operative expectations for Mohs surgery in patients with chronic lymphocytic leukemia: A multicenter retrospective cohort studyCapsule Summary - Remi K. Hamel, MD; Jordan Phillipps, BS; Tariq Nisar, MPH; Elizabeth Hall, MD; Laurin Council, MD; Arash Kimyai-Asadi, MD; Leonard H. Goldberg, MD (Elsevier, 2023)
Background: Patients with chronic lymphocytic leukemia (CLL) are immunocompromised and have both a higher incidence of and more aggressive skin cancers, often requiring treatment with Mohs micrographic surgery. Objective: Characterize operative expectations for Mohs surgery in patients with CLL. Methods: Multicenter retrospective cohort study. Results: One hundred fifty-nine tumors from 99 patients with CLL were matched 1:4 with controls. Cases had higher odds for requiring at least 3 stages during Mohs surgery compared to controls (odds ratio = 1.91; 95% CI [1.21-3.02]; P = .01). The mean number of Mohs stages in cases was 1.97 (±0.92) compared with 1.67 (±0.87) in controls (P = .0001). A regression analysis showed that cases had larger postoperative tumor areas (cm2) versus controls (mean = 5.57 vs 4.47; estimate difference Δβ = 1.10 cm2; 95% CI [0.18-2.03]; P = .02). In logistic regression, cases were twice as likely to receive a flap repair compared to controls (odds ratio = 2.45; 95% CI [1.58-3.8]). Limitations: Retrospective cohort study and lack of histologic subtyping of tumors. Conclusion: Patients with CLL require more Mohs stages to attain clear surgical margins, have larger postoperative defect areas, and require more advanced repair techniques compared to a control population without CLL. These findings are essential for preoperative planning and patient counseling and further support the use of Mohs surgery in patients with CLL.